Valencia bridge fire tests: Validation of simplified and advanced numerical approaches to model bridge fire scenarios. (February 2019) - Alos-Moya, J.; Paya-Zaforteza, I.; Hospitaler, A.; Loma-Ossorio, E.
Highlights: This study calibrates simplified and advanced numerical models of bridge fires. Calibrated from the results of the Valencia bridge fire tests. Simplified models have serious limitations regarding the fire load. Uncertainty studies prove the goodness of the advanced models using CFDs. The study is an important step towards a performance-based approach to bridge fires. Abstract: Bridge fires are a major concern and the subject of many studies that use numerical models. However, experimental studies are still required to test the validity of these numerical models and improve their accuracy. This paper uses temperature results of the Valencia bridge fire tests carried out at the Universitat Politècnica de València, in Valencia (Spain) to calibrate the fire models that constitute the first step in modeling any bridge fire event. The calibration is carried out by both a simplified approach (Heskestad and Hamada's correlation) and advanced numerical models (Computational Fluid Dynamics models built with the Fire Dynamics Simulator –FDS- software). The Valencia bridge fire tests involved four fire scenarios under a composite bridge with Heat Release Rate (HRR) values between 361 and 1352 kW. The results show that applying Heskestad and Hamada's correlation gave good results when used within its limits of application (HRR < 0.764 MW) but did not work well beyond them, which means it would be suitable for planning reduced scale bridge fire tests but not in the analysis of real bridge fires. On the other hand, FDS provides good predictions of the temperatures and can be used to study bridge fire responses. This work is therefore an important step forward in the study of bridge fires and towards the improvement of the resilience of infrastructure networks vis-à-vis fire hazards. It also highlights the problems that can arise in fire tests in the open air, the influence of the wind being of critical importance.